2017
DOI: 10.1111/auar.12187
|View full text |Cite
|
Sign up to set email alerts
|

Application of International Financial Reporting Standards in the Transition Economy of Serbia

Abstract: This paper explores the attitudes of the preparers of financial statements in the emerging economy of Serbia towards International Financial Reporting Standards (IFRS). Our research shows that preparers are mainly satisfied with the quality of IFRS and the environment for IFRS application in Serbia and that they generally support the process of global convergence of financial reporting standards. Nevertheless, we find that there is a need to improve the environment for IFRS application in Serbia, and we identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…The finding that the HC model predominates in subsequent measurement of owner-occupied properties and plant and equipment is consistent with the findings of the research conducted by Obradović et al (2018), which reveals that markets for many assets in Serbia are not sufficiently developed to provide the basis for reliable estimation of FV and that owners and managers of Serbian companies do not have sufficient willingness to engage external experts in the process of measuring financial statements items. This last finding is important because the engagement of such experts is often necessary for adequate FV estimation of PPE items.…”
Section: The Use Of Historical Cost and Fair Valuesupporting
confidence: 82%
“…The finding that the HC model predominates in subsequent measurement of owner-occupied properties and plant and equipment is consistent with the findings of the research conducted by Obradović et al (2018), which reveals that markets for many assets in Serbia are not sufficiently developed to provide the basis for reliable estimation of FV and that owners and managers of Serbian companies do not have sufficient willingness to engage external experts in the process of measuring financial statements items. This last finding is important because the engagement of such experts is often necessary for adequate FV estimation of PPE items.…”
Section: The Use Of Historical Cost and Fair Valuesupporting
confidence: 82%
“…Other papers and researches that deal with the content of the auditor's reports and financial reporting practices in the Republic of Serbia pointed this issue. For example, authors (Obradovic et al, 2018) found that Revaluation of property, plant and equipment and Capitalisation of post-purchase costs of property, plant and equipment are areas that are considered to be particularly complex or problematic by respondents from Serbia. Furthermore, it seems that Serbian business entities also struggle with Disclosures in notes to financial.…”
Section: Discussionmentioning
confidence: 99%
“…; Obradović et al. ; Sucher and Jindrichovska ). Consequently, some non‐compliance may be expected in the first few years of adoption.…”
Section: Compliance With International Standardsmentioning
confidence: 99%